Mengurai Tantangan Dalam Mewujudkan Masyarakat Pesisir yang Tangguh - Alfian, Lalu Muhammad; Mardiana (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2024)
One of the main problems associated with coastal communities in Indonesia is the relatively low utilization of the economic potential of marine resources.  This is indicated by the figure of Indonesia's gross domestic product (GDP) from marine resources in 2022 which only amounted to 2.58% (BPS, 2024). In addition, facts show that most coastal communities are economically weak.  Various efforts have been made to alleviate coastal communities from poverty but have not shown satisfactory results.  This research aims to explore the causes of this from the social and cultural perspective of the local community.  The research method used is a literature study.  The lack of skills other than fishing causes fishermen to be unable to do other businesses during the lean season is one of the findings in this study.  Empowerment programmes aimed at coastal-fisher communities do not run optimally due to attitudes that are still strongly attached to being individual, wasteful, trusting and resigned to circumstances.